Comparing survival outcomes for cervical cancer based on the 2014 and 2018 International Federation of Gynecology and Obstetrics staging systems - Wonkyo Shin; Tae Young Ham; Young Ran Park; Myong Cheol Lim; Young-Joo Won (Scientific Reports, 2021)
Abstract The International Federation of Gynecology and Obstetrics (FIGO) cervical cancer staging system was modified in 2018, introducing new stage IB subdivisions and new lymph node status considerations in stage IIIC. We compared cervical cancer survival outcomes according to the 2014 and 2018 FIGO staging systems. We selected 10% of cervical cancer cases (2010–2015) from the Korean national cancer registry (2010–2015) through a systematic sampling method. We collected information using a collaborative stage data collection system and evaluated the results according to both staging systems. The log-rank test was used to analyze overall survival differences. No significant difference in survival was observed between 2018 subdivisions IB1/IB2/IB3 (P = 0.069), whereas a considerable difference was observed between these subdivisions according to histological subtypes. In the 2018 FIGO staging system, stage IIIC had better survival than stage IIIA/IIIB (P < 0.001). We observed considerable heterogeneity in 2018 stage IIIC related to the corresponding stages of the 2014 staging system (stages IA1–IIIB). The size of the primary cervical mass was related to survival (P < 0.001). In conclusion, using lymph node status to define stage IIIC captured a broad range of prognoses. The inclusion of primary tumor size considerations may improve the staging accuracy of advanced cervical cancer.